Les obligations du courtier d’assurance face à la pratique et à la jurisprudence : 1re partie - Duquette, Raymond (Assurances, 1987)
In the first part of his study, Mr. Duquette examines the liability of the broker in the exercise of his functions. Although, at times, Mr. Duquette may sound quite severe, the broker must understand that he has certain well-defined commitments which he must fulfill within a reasonable period of time. If he does not, he exposes himself to the risk of being sued. This aspect of the subject is very interesting since the author has based himself on specific precedents. As the author suggests, however, we must not hold the broker responsible for all that goes a miss without first ascertaining if he has fulfilled his duties. Mr. Duquette clearly exposes that it is essential that a broker fulfill his functions with care if he wishes to be defended in court and avoid serious liability problems.